Social Sustainability Depends - Ljunggren, Marcus; Renfro, Sebastian (2018)
In many cities worldwide, decaying neighborhoods - residential or post-industrial - undergo urban renewal. Often located close to city centres, these neighborhoods hold the potential to be transformed into new, attractive residential- and mixed-use blocks. However, this type of urban regeneration seems to often lead to increased segregation and gentrification. In the city of Malmö in southern Sweden, the neighborhood Norra Sorgenfri is located. While it is facing a regeneration process, we have noticed several indications of a potential gentrification - an outcome we see as harmful due to its destructive impact on equity and social relations. Therefore, this thesis problematizes gentrification in relation to social sustainability. With Norra Sorgenfri as a case, we aim to answer the questions: How will the City of Malmö’s plans support social sustainability in Norra Sorgenfri? and how could a public space in Norra Sorgenfri be designed to support mixed social use? We have studied Norra Sorgenfri’s likely future development by analyzing the City of Malmö’s plan programme, a complementary interview with a city planner of the City of Malmö involved in the plan programme, through site visits and an analysis of additional material such as published news articles concerning the area. Our theoretical background was primarily theories within critical urban studies and geography on gentrification and social sustainability. Our key findings indicate that the area of Norra Sorgenfri most likely will undergo residential gentrification as a consequence of its urban development. This means that many of the area’s current residents will be forced to relocate. However, the City of Malmö’s plan programme is able to support a socially sustainable use of some of the neighborhood’s public spaces through a well integrated structure, by improving the sense of place, planning for safety and by adding mixed structures that allow different activities and uses. We test our own theoretical assumptions by applying them in a design proposal. Through our theoretical approach, along with the vision of the plan programme, we have designed a public space based on situated knowledge which has taken into consideration the movement of inhabitants. The design supports multiple groups, flexible activities and becomes an example of how public spaces can be designed to engage a diverse user group to interact in a space going through change.